EFFECTIVENESS OF PROVISION OF TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) AND INFRA RED (IR) MODALITY IN CASE OF OSTEOARTHRITIS KNEE - Yoel Kristian Adi Candra; Daniel Saka Pratama; Sima Asmara Dewa Marya Mahardika Putri (Physiotherapy and Physical Rehabilitation Journal, 2022)
Background : Osteoarthritis of the knee is joint disorders knee that causes happening erosion marked joints with existence symptom painful as well as increase functional disability. Functional disability of knee OA patients here is subtraction against activity physique daily caused by pain. Because of that, from a number of research obtained gift modality therapy in the form of TENS and Infra Red effective in reduce knee osteoarthritis pain. Research objective : For knowing influence gift modality TENS and Infrared therapy to knee osteoarthritis condition.Methodology : Overview systematic from three related articles with administration of TENS and Infra Red in the condition of knee osteoarthritis. Results : Modality TENS and Infra Red (IR) therapy can give significant influence for lower pain in knee osteoarthritis. Conclusion : Giving modality TENS and Infrared therapy capable give influence decreased pain.